Залежність вмісту ¹³⁷Cs у рослині від параметрів грунтового розчину - Булавін, Л.А.; Пророк, В.В.; Агєєв, В.А.; Мельниченко, Л.Ю.; Осташко, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Different kinds of rapidly maturing plants were grown simultaneously at experimental sites under natural conditions at the Chornobyl Exclusion Zone. The content of ¹³⁷Cs in a plant and in the corresponding soil solution and the content of the soil solution in soil were measured. We have first established that, for all investigated plants and experimental sites, the ¹³⁷Cs plant uptake is approximately proportional to the concentration of dissolved ¹³⁷Cs in the soil — to the product of the ¹³⁷Cs content in the soil solution and the content of the soil solution per unit volume of soil.